2021
DOI: 10.1111/1365-2745.13715
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential for plant translocations to adapt to a warming world

Abstract: 1. Anthropogenic climate warming is undisputed and yet, there is much that is unknown regarding biological impacts of changing temperature and precipitation, and the management options presented as solutions to biodiversity losses-such as translocations of plants and seeds-are often controversial. This SpecialFocus presents five new studies and two recently published articles in Journal of Ecology and Ecological Solutions and Evidence that analyse the use of existing plant translocations, assess the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Our findings have implications for conservation in our changing world. Managers often have been concerned with maintaining adaptation to local environments of the populations they manage (Dalrymple et al ., 2021). In the Anthropocene, where environments are changing extremely rapidly, a focus on supporting sufficient genetic variation for ongoing adaptation to shifting conditions is important.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have implications for conservation in our changing world. Managers often have been concerned with maintaining adaptation to local environments of the populations they manage (Dalrymple et al ., 2021). In the Anthropocene, where environments are changing extremely rapidly, a focus on supporting sufficient genetic variation for ongoing adaptation to shifting conditions is important.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting long-term monitoring would allow better assessment of the success of a translocation so that valuable insights can be made regarding plant response to climate change (e.g., Fenu et al 2020;Diallo et al 2021;Dalrymple et al 2021;Julien et al 2022b). At the same time, although numerous cases are known nationally or internationally, none of the papers described a failed translocation.…”
Section: Question 1: How Many Translocations (And On What Plant Speci...mentioning
confidence: 99%
“…With limited financial resources currently available globally for conservation and translocation of threatened plants (Dalrymple et al 2021) and increased pressure to prioritise species for conservation (see papers reviewed in Cullen 2012), maximising what limited resources are currently available for plant conservation is critical. Given that anthropogenic climate change (Ciavarella et al 2020) will result in assisted migration being the only option for translocation of many species (Dalrymple et al 2021), understanding the niche that will sustain both adults and seedlings becomes increasingly important when choosing sites outside of their known habitat (Bellis et al 2020). Given that 70% of translocations are unsuccessful (average of results provided in reviews by Godefroid et al 2011, Dalrymple et al 2021, Reiter et al 2016and Silcock et al 2019, large financial savings could be made by modest improvements.…”
Section: Financial Implicationsmentioning
confidence: 99%
“…Given that anthropogenic climate change (Ciavarella et al 2020) will result in assisted migration being the only option for translocation of many species (Dalrymple et al 2021), understanding the niche that will sustain both adults and seedlings becomes increasingly important when choosing sites outside of their known habitat (Bellis et al 2020). Given that 70% of translocations are unsuccessful (average of results provided in reviews by Godefroid et al 2011, Dalrymple et al 2021, Reiter et al 2016and Silcock et al 2019, large financial savings could be made by modest improvements. On the basis of the assumptions of costs of translocating a population in Zimmer et al (2019), broken down into a cost per propagule, we showed that combining the optimal microsite niche for both adult survival and recruitment can lead to a cost saving of A$31 611 ± $15 067 to $179 900 ± $85 750 for a single threatened species.…”
Section: Financial Implicationsmentioning
confidence: 99%